2013
DOI: 10.1089/jpm.2012.0324
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota Rural Palliative Care Initiative: Building Palliative Care Capacity in Rural Minnesota

Abstract: Palliative care development is necessary in rural communities, and envisioning a program that combines structure, accountability, customized guidance, tools, and networking across settings is essential for success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…A program-development evaluation survey assessed the benefits of the Minnesota Rural Palliative Care Initiative and satisfaction with participation. 17 All the program components were rated well and an increase was seen in participant knowledge of pain management and goals of care discussions. 17 Fink et al 16 used an investigator-developed needs assessment instrument to determine awareness, knowledge, barriers, and access to resources of palliative care services in 236 Rocky Mountain-area rural hospitals.…”
Section: Needs Assessmentmentioning
confidence: 96%
See 2 more Smart Citations
“…A program-development evaluation survey assessed the benefits of the Minnesota Rural Palliative Care Initiative and satisfaction with participation. 17 All the program components were rated well and an increase was seen in participant knowledge of pain management and goals of care discussions. 17 Fink et al 16 used an investigator-developed needs assessment instrument to determine awareness, knowledge, barriers, and access to resources of palliative care services in 236 Rocky Mountain-area rural hospitals.…”
Section: Needs Assessmentmentioning
confidence: 96%
“…17 All the program components were rated well and an increase was seen in participant knowledge of pain management and goals of care discussions. 17 Fink et al 16 used an investigator-developed needs assessment instrument to determine awareness, knowledge, barriers, and access to resources of palliative care services in 236 Rocky Mountain-area rural hospitals. They found that 99% of health care professionals were familiar with the palliative care concept, 76% had a contract with a local hospice organization, 72% participated in a program to promote advancecare planning, 56% had access to palliative care resources, and 72% had palliative care education offered in the past year.…”
Section: Needs Assessmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Allied health practitioners working in rural areas also report being under-prepared and lacking access to continuing education [24,25]. The recommended educational strategies for these groups include conducting a needs analysis and designing context specific programs [3,26]. Local delivery of education which takes into account contextual factors can strengthen existing community expertise and commitment, enabling service providers to respond to community needs in a sustainable way [2].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, palliative care services have been successfully integrated into ambulatory clinics, most notably oncology practices (3). Efforts have been successfully undertaken to train a range of providers (e.g., nurses and social workers) how to deliver key components of palliative care in ambulatory settings (7). In addition, palliative care is now provided through some home health care agencies (810).…”
mentioning
confidence: 99%